Assessment of the bioclimatic conditions of a popular playground by the microclimate model ENVI-MET - Égerházi László (Acta climatologica, 2012)
The paper introduces a thermal comfort examination carried out in a well-attended playground located in the city centre of Szeged (Hungary). The aim of this study is to find the optimal land cover and vegetation options of the study area by means of numerical simulations. For this evaluation the modelled micro- and bioclimatological conditions of a typical summer day (12th July 2011) were analyzed. The thermal and radiation environments of the playground were quantified by one of the most popular bioclimatological comfort index Predicted Mean Vote (PMV) and the Mean Radiant Temperature (Tmn). The simulations of the investigated parameters were performed by the microclimate model ENVI-met. The obtained results proved that the modelled area provided a variety of thermal conditions for the visitors due primarily to the different land covers. Moreover this paper emphasizes the important effect of the vegetation on the human thermal sensation.